Has the exchange depreciation contributed to exports? The Japanese case - Kurihara, Yutaka (Archives of Business Research, 2020)
Many people believe that depreciation of exchange rate promotes exports and leads to economic growth. Export-oriented countries sometimes become very nervous about currency appreciation. This study examines whether or not the Japanese yen’s depreciation has increased volume of exports after Abenomics, which flowed a large amount of capital into the domestic markets to boost the economy. The Japanese yen has depreciated according to quantitative easing, however, whether or not the volume of exports has increased is not certain. Empirical results of this study show that there is not a strong relationship between currency depreciation of the yen and Japanese exports. Also, elasticity, the total percentage changes in trade divided by the total percentage changes in exchange rates, is calculated for main international trade partners for Japan. The results are different for each country. The shock on the exchange rate appears and continues after some time passes.